Ionospheric Delay Phase Estimation and Correction for Multiple-Aperture InSAR: Azimuth Group Phase Delay Method - Wang, Quanling; Hu, Jun; Guo, Aoqing; Gui, Rong (IEEE transactions on geoscience and remote sensing, 2024)
Multiple-aperture interferometric synthetic aperture radar (MAI) technology can obtain the deformation of the surface along the azimuth direction, which makes up for the limitations of traditional interferometric synthetic aperture radar (InSAR) technology. However, the MAI measurement is vulnerable to the ionosphere, which makes the ionospheric delay mixed with the surface deformation, resulting in a serious reduction of the accuracy of the azimuth measurement. In this article, a method for correcting the azimuth ionospheric delay phase is proposed based on the relationship between the ionospheric delay phase and the group phase delay offset, termed by the azimuth group phase delay (AGPD) method. This approach accommodates large-scale deformation fields, facilitating a more comprehensive acquisition of ionospheric information. This method is first employed to reconstruct the coseismic deformation field associated with the 2021 Maduo earthquake. After ionospheric correction, the root mean square errors (RMSEs) between GNSS and MAI measurements decrease from 0.08 to 0.04 m. Then, the results from the Alaska case demonstrate the method's ability in the identification of intricate ionospheric stripe patterns. Comparative analysis against the existing azimuth ionospheric error correction methods indicates a significant improvement of above 50%.